Take a stand against ageism: quality of life among elderly in a rural area of Himachal Pradesh - Chawla, Bharti; Chawla, Sumit; S. K., Shashikantha; Kaur, Harpreet; Kumar, Shashi; Aggarwal, Satish (International Journal Of Community Medicine And Public Health, 2018)
Background: Quality of life (QOL) among elderly is an important area of concern which reflects the health status and well-being of this vulnerable population. The WHOQOL-BREF contains a total of 26 questions which measures QOL is being used in this study. Methods: It is a community based observational study with cross-sectional design carried out on 100 elderly (60+year age) in a rural area of Solan district using pre-designed, pretested and semi-structured interview schedule, which is based on WHOQOL-BREF standard quality of life questionnaire. Appropriate statistical tests were used for analysis using SPSS software. Results: Majority 60% of the subjects were in the age group of 60-70 years, 62% of them were males and 38% of them were females. The mean score value of physical domain, psychological growth, social relations and environment domain among the subjects was found to be 52.50±10.56, 52.86±13.25, 61.15±16.06 and 63.92±11.10 respectively. The mean score of all four domains was found higher among age group 60-70 than age group >70 and It was statistically significant in social domain with p value of 0.017. By gender, mean score of all four individual domains was found higher among males as compared to females but this difference was not statistically significant. Conclusions: The overall quality of life was poor among the study subjects. The subjects who were illiterate, unmarried/widow/widower/divorced/separated, belonged to nuclear family had poor quality of life compared to those who were literate married and belonged to joint family. Males had comparatively better quality of life compared to females in the study area.